Features of Optimal Modeling of Tax Mechanisms in the Leveling System of Environmental and Food Security Taking into Account Inter-Industry Externalities - SHOKHNEKH, Anna V.; SKITER, Natalya N.; ROGACHEV, Aleksey F.; PLESCHENKO, Tatyana V. (Journal of Environmental Management and Tourism, 2017)
The article presents approaches to the optimal modeling of tax mechanisms in the leveling system of environmental and food security taking into account inter-industry externalities, as well as introduces the indicators of optimal modeling in the course of leveling the negative and positive significant influences on the balance of the ecosystem.